Wujud Kasih Sayang Ibu Dalam Seni Patung Abstrak - Aulia Darma, Dra. Lisa Widiarti, M.Sn., Drs. Irwan, M.Sn. (Serupa The Journal of Art Education, 2018)
The purpose of this final paper is to visualize the expression of mother'saffection in the form of abstract figurative sculpture by printing technique(cashting) by using five stages: preparation, elaboration, synthesis, conceptrealization, and completion.After performing a series of long creation process then created 7 pieces ofsculpture, including: '' Beginnings '', '' Long Waiting '', '' Sacrifice Mother '','' Love '', '' Mother Love Expression '' , '' Educating '', and '' Sincerity ''. It is hopedthat the final work will be useful for art students, as an appreciation andcomparative work to create better sculpture in the future.Keywords: Mother, Sculpture, Printing Technique (cashting)